Gene expression analyses reveal metabolic specifications in acute O(2)‐sensing chemoreceptor cells - Gao, Lin (J Physiol, 2017)
KEY POINTS: Glomus cells in the carotid body (CB) and chromaffin cells in the adrenal medulla (AM) are essential for reflex cardiorespiratory adaptation to hypoxia. However, the mechanisms whereby these cells detect changes in O(2) tension are poorly understood. The metabolic properties of acute O(2)‐sensing cells have been investigated by comparing the transcriptomes of CB and AM cells, which are O(2)‐sensitive, with superior cervical ganglion neurons, which are practically O(2)‐insensitive. In O(2)‐sensitive cells, we found a characteristic prolyl hydroxylase 3 down‐regulation and hypoxia inducible factor 2α up‐regulation, as well as overexpression of genes coding for three atypical mitochondrial electron transport subunits and pyruvate carboxylase, an enzyme that replenishes tricarboxylic acid cycle intermediates. In agreement with this observation, the inhibition of succinate dehydrogenase impairs CB acute O(2) sensing. The responsiveness of peripheral chemoreceptor cells to acute hypoxia depends on a ‘signature metabolic profile’. ABSTRACT: Acute O(2) sensing is a fundamental property of cells in the peripheral chemoreceptors, e.g. glomus cells in the carotid body (CB) and chromaffin cells in the adrenal medulla (AM), and is necessary for adaptation to hypoxia. These cells contain O(2)‐sensitive ion channels, which mediate membrane depolarization and transmitter release upon exposure to hypoxia. However, the mechanisms underlying the detection of changes in O(2) tension by cells are still poorly understood. Recently, we suggested that CB glomus cells have specific metabolic features that favour the accumulation of reduced quinone and the production of mitochondrial NADH and reactive oxygen species during hypoxia. These signals alter membrane ion channel activity. To investigate the metabolic profile characteristic of acute O(2)‐sensing cells, we used adult mice to compare the transcriptomes of three cell types derived from common sympathoadrenal progenitors, but exhibiting variable responsiveness to acute hypoxia: CB and AM cells, which are O(2)‐sensitive (glomus cells > chromaffin cells), and superior cervical ganglion neurons, which are practically O(2)‐insensitive. In the O(2)‐sensitive cells, we found a characteristic mRNA expression pattern of prolyl hydroxylase 3/hypoxia inducible factor 2α and up‐regulation of several genes, in particular three atypical mitochondrial electron transport subunits and some ion channels. In addition, we found that pyruvate carboxylase, an enzyme fundamental to tricarboxylic acid cycle anaplerosis, is overexpressed in CB glomus cells. We also observed that the inhibition of succinate dehydrogenase impairs CB acute O(2) sensing. Our data suggest that responsiveness to acute hypoxia depends on a ‘signature metabolic profile’ in chemoreceptor cells.